3D PRINTING DALAM PEMBUATAN PROSTETIK DAN IMPLAN KESEHATAN - Gunawan Widjaja (CV. ADIBA AISHA AMIRA, 2026)
3D printing technology has revolutionised healthcare, particularly in prosthetics and implants. This research examines the role and impact of 3D printing in developing medical solutions tailored to individual patient needs. The method used included a literature review. Results show that 3D printing enables more accurate, efficient and aflordable prosthetics and implants. The technology also oflers high design flexibility, enabling the creation of complex structures that are difficult to achieve with conventional methods. In addition, the integration of biocompatible materials and sensor technology opens up opportunities for more functional and responsive implants. Despite challenges such as regulation and standardisation, 3D printing has the potential to change the paradigm in healthcare, improve patients' quality of life, and pave the way for future medical innovations. Further research is needed to optimise materials, improve manufacturing precision, and address ethical and accessibility issues.